Causes of Kawasaki Disease—From Past to Present - Nagata, Satoru (Frontiers in Pediatrics, 2019)
Kawasaki disease (KD) is a multisystem vasculitis that primarily affects the coronary arteries of young children. The causes of KD remain a mystery. It is suspected that some sort of infectious agent is involved because KD has epidemicity and seasonality. That said, the incidence of the disease is high among Japanese people, so it can be speculated that the hosts may have some sort of genetic characteristic that leaves them susceptible to KD.　Various theories regarding the etiology have been asserted, such as the infectious vasculitis theory, autoantigen theory, superantigen theory and RNA virus theory; however, none of them have been able to overcome this epidemicity. Taking into consideration the knowledge gained from previous reports, the best scenario explaining the pathogenesis is "individuals with certain genetic backgrounds are affected by microorganisms which trigger KD.” In this article, the pathogenesis of KD is discussed with a focus on the microorganisms mentioned above, along with the previous and current hypotheses as well as my own opinion.